Automobile Biographies : An Account of the Lives and the Work of Those Who Have Been Identified with the Invention and Development of Self-Propelled Vehicles on the Common Roads - Weeks, Lyman Horace (Salt Lake City, UT : Project Gutenberg, 2013)
"Automobile Biographies" by Lyman Horace Weeks is a historical account written in the early 20th century. The book chronicles the lives and innovations of key figures associated with the invention and evolution of self-propelled vehicles. It provides insights into the technical challenges these pioneers faced and their contributions to the automotive industry. The opening of the book sets the stage by discussing the rich history surrounding the development of automobiles, beginning with early concepts and inventions that date back several centuries. It highlights notable inventors and engineers, such as Nicholas Joseph Cugnot, Richard Trevithick, and Oliver Evans, who made significant strides in mechanizing transportation. The foreword also explains the extensive research undertaken to compile these biographies, aiming to not only record these innovators' great achievements but also shed light on the advancements and societal implications brought forth by their work, ultimately leading up to the modern automobile. (This is an automatically generated summary.)
Release date is 2013-01-21
E-text prepared by Chris Curnow and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://archive.org)
Keywords: Automobiles -- History